Efficacy of Microbials as Insecticides for the Management of Tomato (Lycopersicon esculentum) Fruitworm, Helicoverpa armigera (Hubner) (The Agriculturists, 2014)
The experiment was conducted at the experimental field of Entomology Division, BARI, Gazipur during Rabi 2007-08. Two microbial insecticides HaNPV @ 0.4ml/L and Bt @ 2g/L along with their combination were tested against H. armigera. The lowest fruit infestation, both in number and weight, was obtained from treatment HaNPV and Bt alternate spraying (11.78%, 9.64%), followed by Bt (13.25%, 10.85%) and HaNPV (17.67%, 13.11%). The highest fruit yield (16.92 t/ha) was obtained from HaNPV and Bt alternate spraying plots followed by Bt (16.65 t/ha) and HaNPV (14.73 t/ha). In case of MBCR, the highest MBCR was obtained from HaNPV and Bt alternate spraying (5.30) followed by HaNPV (4.46) and Bt (3.37). DOI: http://dx.doi.org/10.3329/agric.v12i1.19583 The Agriculturists 2014; 12(1) 68-74